Shuffling algorithms for automatic generator question paper system. - Mohd Jamail, Nor Shahida; Md Sultan, Abu Bakar (Canadian Center of Science and Education (CCSE), 2010)
Examination process is important activities for educational institutions to evaluate student performance. Thus the quality of the exam questions would determine the quality of the students produced by the institutions. Preparing exam questions is challenges, tedious and time consuming for the instructors. Usually the instructors keeping their own test bank in some form to help them prepare future exams. Current technologies help the instructors to store the questions in computer databases. The issue arise is how the current technologies would also help the instructors to automatically generate the different sets of questions from time to time without concern about repetition and duplication from the pass exam while the exam bank growing. This paper describes the usage of shuffling algorithm in an Automatic Generator Question paper System (GQS) as a randomization technique for organising sets of exam paper. The results indicate shuffling algorithm could be used to overcome randomization issue for GQS.